Low-velocity ice impact response and damage phenomena on steel and CFRP sandwich composite. (April 2022) - Banik, Arnob; Zhang, Chao; Khan, M.H.; Wilson, Matt; Tan, K.T.
Highlights: Low-velocity ice impact on steel and CFRP sandwich composites are investigated. Customized ice impactor is fabricated using a 3D printed rubber mold. Freezing temperature and duration are observed to influence ice damage pattern. Higher absorbed energy is needed to destroy ice impactor for sandwich composite. Ice impactor fragmentation is characterized as crushing, spalling and splitting. Abstract: This study investigates the low-velocity impact (LVI) response of ice impactor on steel and carbon fiber reinforced polymer (CFRP) sandwich composite. This research explores the effect of impactor's shape and length at different impact velocity by preparing customized conical and cylindrical ice impactors. Ice impactors that are frozen at -12 °C for 48 h are found to have the highest occurrence of partial damage, while ice impactors conditioned at -22 °C for 72 h experienced full damage. Although higher peak force is observed during ice-steel interaction, greater displacement and absorbed energy are evident in ice-composite impact. Results also show that full damage of ice impactor is more prominent for sandwich composite specimens, while partial damage is commonly seen in steel specimens. This is attributed to multiple hits and higher ratio of collision velocity during impact on sandwich composite. Damage type occurrences also vary depending on shape, length, and impact velocity of the ice impactors. Presence of pre-existing cracks during freezing as well as variation in stress level at the impact region influence the strength of the ice impactors. Matrix crack and facesheet dent are observed as the dominant damage mechanism in composite using X-ray micro-computed tomography. Different ice fragmentation processes are also characterized in this study.